Induction of Type I Interferons by Therapeutic Nanoparticle-Based Vaccination Is Indispensable to Reinforce Cytotoxic CD8+ T Cell Responses During Chronic Retroviral Infection - Knuschke, Torben; Rotan, Olga; Bayer, Wibke; Kollenda, Sebastian; Dickow, Julia; Sutter, Kathrin; Hansen, Wiebke; Dittmer, Ulf; Lang, Karl S.; Epple, Matthias; Buer, Jan; Westendorf, Astrid M. (Frontiers in Immunology, 2018)
T cell dysfunction and immunosuppression are characteristic for chronic viral infections and contribute to viral persistence. Overcoming these burdens is the goal of new therapeutic strategies to cure chronic infectious diseases. We recently described that therapeutic vaccination of chronic retrovirus infected mice with a calcium phosphate (CaP) nanoparticle-based vaccine carrier, functionalized with CpG and viral peptides is able to efficiently reactivate the CD8+ T cell response and improve the eradication of virus infected cells. However, the mechanisms underlying this effect were largely unclear. While type I interferons (IFNs I) are considered to drive T cell exhaustion by persistent immune activation during chronic viral infection, we here describe an indispensable role of IFN I induced by therapeutic vaccination to efficiently reinforce cytotoxic CD8+ T cells (CTL) and improve control of chronic retroviral infection. The induction of IFN I is CpG dependent and leads to significant IFN signaling indicated by upregulation of interferon stimulated genes (ISG). By vaccinating chronically retrovirus-infected mice lacking the IFN I receptor (IFNAR-/-) or by blocking IFN I signaling in vivo during therapeutic vaccination, we demonstrate that IFN I signaling is necessary to drive full reactivation of CTLs. Surprisingly, we also identified an impaired suppressive capability of regulatory T cells (Treg) in the presence of IFNα, which implicates an important role for vaccine induced IFNα in the regulation of the T cell response during chronic retroviral infection. Our data suggest that inducing IFN I signaling in conjunction with the presentation of viral antigens can reactivate immune functions and reduce viral loads in chronic infections. Therefore, we propose CaP nanoparticles as potential therapeutic tool to treat chronic infections.